New farmers and eco-social transformation for inner areas: processes of innovation and social construction of quality in Trentino Alto-Adige and Liguria - Uleri, Francesca; Elsen, Susanne; Piccoli, Alessandra (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2022)
Despite perpetuate dynamics of marginalization-peripheralization which have characterized the nuanced profile of the Italian inner areas, currently, it is possible to intercept in these territories marked by significant processes of deagrarianization and depeasantization, a parallel trend of return to the land. This (re)discovered attraction for the “art of farming” in the “difficult countryside” reflects the emergence of a new demand for stability addressed to these territorial contexts by new generations of farmers who aspire to start with a newly emerging entrepreneurial idea or in some cases, to continue a previous family tradition. The article focuses on the role that young farmers have in triggering a process of territorial regeneration and eco-social transformation in inner areas. In doing so, the analysis develops through the identification of the sub-processes of innovation and social construction of the quality of the products and services provided by the new generations of farmers in different Alpine valleys in Trentino Alto-Adige and Liguria. The activity of new farmers contributes to make emerge inner areas not as passive perceivers of macro-economic dynamics, rather as active and dynamic social spaces within which territorial uniqueness regains value in new business strategies, also influencing social representation of quality. Furthermore, with the activation of specific innovation strategies, farms diversify their functions thus contributing to reshape the profile of the territory and significantly determine its capacity to connect with the “outside”.